1993
DOI: 10.1111/j.1365-2796.1993.tb00762.x
|View full text |Cite
|
Sign up to set email alerts
|

Sonography of the achilles tendon in hypercholesterolaemia

Abstract: We conclude that ultrasonography is a sensitive method of detecting xanthomas that reveals the altered tendon structure even in xanthomatous tendons of normal thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
3

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 9 publications
1
15
0
3
Order By: Relevance
“…These gender differences have been observed in other studies 11,14,16,26 and may be explained by the usually higher musculoskeletal development in men. Supporting prior results in control subjects, 26 AT size was related to body weight, a plausible finding given the body support function that AT plays in skeletal physiology.…”
Section: Discussionmentioning
confidence: 46%
See 3 more Smart Citations
“…These gender differences have been observed in other studies 11,14,16,26 and may be explained by the usually higher musculoskeletal development in men. Supporting prior results in control subjects, 26 AT size was related to body weight, a plausible finding given the body support function that AT plays in skeletal physiology.…”
Section: Discussionmentioning
confidence: 46%
“…Tendon xanthomas are a key feature for the clinical diagnosis of FH, 8,10 but identification by physical examination is subjective and based on clinical experience, and may be difficult in borderline cases. Ultrasonography has been shown to accurately measure AT thickness, which is enlarged when xanthomas are present [11][12][13][14][15][16] and, using state-of-the-art musculoskeletal sonography and a careful technique, it also detects echostructural abnormalities that are diagnostic of xanthoma in tendons not injured previously. 10 -15,22 By using this technique, we observed no sonographic AT xanthomas in either control or non-FH subjects, but detected them in a sizeable proportion of FH subjects (40% and 24% in those with and without DNA diagnosis, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinically, this can lead to the development of a tendinopathy as evidenced by the presence of pain and functional limitation for periods longer than six weeks, without relief from anti-inflammatory medication. The accompanying disruption of tissue organization results in a more isotropic speckle pattern, with visual analysis suggesting reduced organization of the parallel striations and localized regions of hypoechogenicity [4]- [7]. It has been shown that changes in ultrasound radio-frequency (RF) spectra may be used to indicate damage in equine tendon [8], and discriminate age in human tendon [9].…”
mentioning
confidence: 99%